Composite reverse osmosis membrane and preparation method thereof
By using acrylate nanopolymers in composite reverse osmosis membranes for interfacial polymerization and UV curing, a polymer interpenetrating network structure is formed, which solves the problem of reduced desalination rate and flux of existing membranes after frequent acid and alkali cleaning. Improvements in high-throughput and durability performance are achieved.
Patent Information
- Application Number
- CN202411760063.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-01-21
AI Technical Summary
The existing composite reverse osmosis membranes are difficult to maintain after frequent acid and alkali cleaning, and the flux also decreases, resulting in a shortened service life and poor effect in scenarios of high-polluted wastewater reuse.
By adding acrylate nanopolymer to the aqueous solution and performing interfacial polymerization on the porous support membrane, a polyamide separation layer is formed, and a polymer interpenetrating network structure is formed through UV curing to improve the durability and permeability of the membrane. quantity.
It achieves the high flux and chemical cleaning resistance of the composite reverse osmosis membrane, which can maintain high desalination rate and water flux after frequent acid and alkali cleaning in highly polluted wastewater reuse scenarios, and extend the service life of the membrane.
Smart Images

Figure BDA0005167395370000071 
Figure BDA0005167395370000131 
Figure BDA0005167395370000132
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water treatment, and in particular to a high-flux and enhanced-cleaning-resistant composite reverse osmosis membrane and a preparation method thereof. Background Art
[0002] Usually, a composite reverse osmosis membrane is a single membrane formed by compounding different materials such as polyester non-woven fabric, polysulfone, polyamide, etc., wherein the polyamide layer plays a role of separation. As described in the patents of Cadotte et al.: US4277344A and US5658460A, the polyamide layer is obtained by the interfacial polycondensation reaction between multifunctional amine monomers and multifunctional acyl halide monomers.
[0003] Composite reverse osmosis membranes are used in many scenarios such as municipal water, surface water, wastewater reuse, and seawater desalination. This membrane can be generated by interfacial polymerization of monomers in the aqueous phase and monomers in the organic phase on a porous support membrane. Composite reverse osmosis membranes are used in special scenarios that require flux and resistance to frequent acid and alkali cleaning, such as in the reuse of wastewater with extremely high pollutants. In order to reduce energy consumption, a variety of materials and chemical additives have been added to composite reverse osmosis membranes to increase flux without reducing retention performance. During the use of such membranes, the water inlet pressure will decrease due to the increase in flux, and the electricity cost will be reduced, but the surface of the composite membrane will also be contaminated, causing the deposition of pollutants, resulting in a decrease in water flux, which can be restored by cleaning, but frequent cleaning will cause the retention performance of the membrane to decrease, and even shorten the service life.
[0004] CN101791522 discloses a method for preparing a hybrid reverse osmosis composite membrane containing carbon nanotubes, and carbon nanotubes are added to a synthetic monomer solution. CN102553458A discloses a large-flux anti-pollution composite reverse osmosis membrane and a preparation method thereof, which is formed by cross-linking epoxy group-containing monomers and polyol monomers, and then subjected to high-temperature treatment to form a coating on the surface of a polyamide functional layer. The composite reverse osmosis membranes of the above patent documents are all intended to improve the flux and reduce the effect of pollution, but lack targeted structural regulation for maintaining the desalination rate after frequent cleaning. It is necessary to further improve the flux while maintaining or improving the interception performance after frequent acid and alkali cleaning, and the technology for the improved composite membrane to be suitable for commercial manufacturing. Summary of the invention
[0005] In order to solve the above problems, the present invention aims to provide a composite reverse osmosis membrane with high flux and resistance to chemical cleaning and a preparation method thereof.
[0006] In order to achieve the purpose of the present invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a composite reverse osmosis membrane, comprising:
[0008] (1) adding a polyamine compound and an additive into water, stirring and dissolving them at room temperature to prepare an aqueous phase solution;
[0009] Adding polyacyl chloride compound and photoinitiator into non-polar solvent, stirring and dissolving at room temperature to prepare organic phase solution;
[0010] (2) immersing the porous support layer in the aqueous solution prepared in step (1);
[0011] (3) contacting the porous support layer treated in step (2) with the organic phase solution to perform interfacial polymerization, thereby forming a polyamide separation layer on the surface of the porous support layer, and the polyamide separation layer is cured by ultraviolet light to obtain a composite reverse osmosis membrane;
[0012] Wherein, the additive in step (1) is selected from acrylic ester nanopolymers.
[0013] In some embodiments, the amount of the acrylic ester nanopolymer added is 0.1 to 15 wt %, preferably 1 to 10 wt %, based on the total weight of the aqueous solution;
[0014] The particle size of the acrylic ester nanopolymer is 10 to 200 nm, preferably 30 to 150 nm, and the glass transition temperature is 10 to 80° C., preferably 20 to 60° C.
[0015] In some embodiments, the acrylic ester nanopolymer is prepared by reacting a carboxyl monomer and / or a hydroxyl monomer with an unsaturated double bond-containing monomer;
[0016] Based on the total amount of raw materials added being 100 wt %, the total amount of the carboxyl monomer and the hydroxyl monomer added is 0.5 to 15 wt %.
[0017] In some specific embodiments, the unsaturated double bond-containing monomer is selected from one or more of styrene, acrylate, methacrylate, vinyl acetate, polyethylene glycol methyl ether acrylate, polyethylene glycol methyl ether methacrylate or N-vinyl pyrrolidone;
[0018] The carboxyl monomer is selected from one or more of acrylic acid, methacrylic acid or itaconic acid;
[0019] The hydroxy monomer is selected from one or more of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate or hydroxypropyl methacrylate.
[0020] In some embodiments, the polyamine compound is selected from one or more of p-phenylenediamine, m-phenylenediamine, ethylenediamine, propylenediamine or piperazine;
[0021] The polyacyl chloride compound is selected from one or more of trimesoyl chloride, trimellitic acid chloride or terephthaloyl chloride;
[0022] The non-polar solvent is at least one selected from ethylcyclohexane, octane, nonane, decane, ISOPAR-E, ISOPAR-L and ISOPAR-G.
[0023] In a specific embodiment of the present invention, the aqueous phase solution further includes a surfactant and a desiccant;
[0024] Preferably, the surfactant and the desiccant are added in an amount of 0.1 to 10 wt % based on the total weight of the aqueous solution;
[0025] More preferably, the surfactant is selected from nonionic surfactants, ionic surfactants and zwitterionic surfactants.
[0026] In some embodiments, based on the total weight of the organic phase solution, the amount of the polyacyl chloride compound added is 0.05 to 1 wt%, and the amount of the photoinitiator added is 0.05 to 5 wt%;
[0027] Preferably, the photoinitiator is selected from benzophenone derivatives, alkyl aromatic ketone derivatives, benzil derivatives or thioxanthone derivatives.
[0028] In step (2) of the preparation method of the present invention, the porous support layer is immersed in the aqueous solution for 10 to 60 seconds, and then the excess solution on the membrane surface is removed. Specifically, the porous support layer is selected from a polysulfone porous support layer. Preferably, the thickness of the porous support layer is 20 to 100 μm.
[0029] In some embodiments, in the ultraviolet light curing treatment of step (3), the ultraviolet light irradiation time is 1 second to 20 minutes.
[0030] In a second aspect, the present invention provides a composite reverse osmosis membrane prepared by the above method. When the composite membrane is exposed to 2000ppm NaCl in deionized water at 25±0.5°C, pH=7.5±0.2 and a pressure of 1.55±0.02MPa, it exhibits a water flux of at least 35gfd and a NaCl removal rate of at least 99.3%.
[0031] The technical solution provided by the present invention has the following beneficial effects:
[0032] The composite reverse osmosis membrane provided by the present invention undergoes interfacial polymerization of polyamine compounds and polyacyl chloride compounds during the preparation process to form a separation functional layer on a porous support membrane. The membrane is irradiated with ultraviolet light during or after the reaction process to form a composite reverse osmosis membrane with increased flux, resistance to frequent acid and alkali cleaning, and high chemical durability. The composite reverse osmosis membrane is particularly suitable for scenarios where highly polluted wastewater needs to be frequently cleaned, such as steel, printing and dyeing, and chemical industry reclaimed water reuse.
[0033] The method of the present invention increases the water permeation channel by adding acrylate nanopolymers in the water phase through the space occupying effect of nanoparticles during the interfacial reaction film forming process, and at the same time, the polymer nanoparticles introduce hydrophilic groups such as carboxyl and hydroxyl groups to further increase the water permeation rate. After the initial interfacial reaction is completed, the nanopolymers are further cross-linked by ultraviolet curing to form a polymer interpenetrating network structure, which can withstand frequent acid-base chemical cleaning and improve the durability of the composite film. DETAILED DESCRIPTION
[0034] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the invention belongs. The term "and / or" as may be used herein includes any and all combinations of one or more of the associated listed items.
[0036] The method for preparing a composite reverse osmosis membrane provided by the present invention comprises:
[0037] (1) adding a polyamine compound and an additive into water, stirring and dissolving them at room temperature to prepare an aqueous phase solution;
[0038] Adding polyacyl chloride compound and photoinitiator into non-polar solvent, stirring and dissolving at room temperature to prepare organic phase solution;
[0039] (2) immersing the porous support layer in the aqueous solution prepared in step (1);
[0040] (3) contacting the porous support layer treated in step (2) with the organic phase solution to perform interfacial polymerization, thereby forming a polyamide separation layer on the surface of the porous support layer, and the polyamide separation layer is cured by ultraviolet light to obtain a composite reverse osmosis membrane;
[0041] Wherein, the additive in step (1) is selected from acrylic ester nanopolymers.
[0042] In some specific embodiments, based on the total weight of the aqueous solution, the added amount of the polymer nanoparticles is 0.1-15wt%, preferably 1-10wt%, for example, 2wt%, 4wt%, 6wt%; the particle size of the polymer nanoparticles is 10-200nm, preferably 30-150nm, for example, 40nm, 70nm, 100nm, 120nm; the glass transition temperature (Tg) is 10-80°C, preferably 20-60°C, for example, 30°C, 40°C, 50°C.
[0043] In the present invention, the acrylic ester nano polymer is polymerized by unsaturated double bond-containing monomers and carboxyl monomers and / or hydroxyl monomers. By introducing hydrophilic monomers such as carboxyl and hydroxyl groups, the solubility parameter of the polymer can be increased, which is conducive to water molecules passing through the separation layer to increase the water flux. Specifically, the polymerization method can be selected from emulsion polymerization, solution polymerization, suspension polymerization and bulk polymerization, preferably emulsion polymerization, which is more effective for controlling the particle size of nanoparticles, and the obtained product can be used directly. This method is well known in the field of polymer synthesis, and can be found in the free radical polymerization and polymerization method section of the fifth edition of "Polymer Chemistry" edited by Pan Zuren.
[0044] In some specific embodiments, based on the total amount of raw materials added (including carboxyl monomers, hydroxyl monomers and monomers containing unsaturated double bonds) as 100wt%, the total amount of carboxyl monomers and / or hydroxyl monomers added is 0.5-15wt%, for example, 1wt%, 3wt%, 5wt%, 8wt%, 12wt%.
[0045] In some more specific embodiments, the unsaturated double bond-containing monomer is selected from one or more of styrene, acrylate, methacrylate, vinyl acetate, polyethylene glycol methyl ether acrylate, polyethylene glycol methyl ether methacrylate or N-vinyl pyrrolidone;
[0046] The carboxyl monomer is selected from one or more of acrylic acid, methacrylic acid or itaconic acid;
[0047] The hydroxy monomer is selected from one or more of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate or hydroxypropyl methacrylate.
[0048] In a specific embodiment of the preparation method of the present invention, the polyamine compound is selected from one or more of p-phenylenediamine, m-phenylenediamine, ethylenediamine, propylenediamine or piperazine; the polyacyl chloride compound is selected from one or more of trimesoyl chloride, trimellitic acid chloride or terephthaloyl chloride.
[0049] In some specific embodiments, the aqueous solution further adds a surfactant and a desiccant; preferably, based on the total weight of the aqueous solution, the amount of the surfactant and the desiccant added is 0.1 to 10 wt%; more preferably, the surfactant is selected from nonionic surfactants, ionic surfactants and zwitterionic surfactants, specifically selected from sodium dodecyl sulfate, alkyl ether sulfates, alkyl ether carboxylates and aromatic sulfonates, preferably sodium dodecyl sulfate (SLS). The desiccant is selected from one or more of glycerol, citric acid, triethylamine camphorsulfonate, triethylamine benzenesulfonate or sucrose, preferably triethylamine camphorsulfonate.
[0050] In some specific embodiments, based on the total weight of the organic phase solution, the amount of the polyacyl chloride compound added is 0.05-1wt%, and the amount of the photoinitiator added is 0.05-5wt%; the photoinitiator is selected from benzophenone derivatives, alkyl aromatic ketone derivatives, benzil derivatives or thioxanthone derivatives, and can be specifically selected from benzophenone, 4-methylbenzophenone, 2,4,6-trimethylbenzophenone, 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl benzophenone and 2,4,6-trimethylbenzoylphosphine oxide.
[0051] In some specific embodiments, in step (2), the porous support layer is immersed in the aqueous solution for 10 seconds to 60 seconds; then, the excess solution on the surface of the porous support layer is removed, specifically by a pressure roller, an air knife or a dryer.
[0052] The porous support layer used in the present invention comprises a substrate and a porous support layer, wherein the substrate can be a polyester non-woven fabric, and the material of the porous support layer can be polysulfone. Specifically, the porous support layer can be prepared in the following manner: polysulfone is dissolved in a dimethylformamide (DMF) solvent and applied to the surface of the non-woven fabric by casting, scraping, coating, etc., and then the porous support layer is formed by a non-solvent to phase inversion method; more specifically, the thickness of the porous support layer is 20 to 100 μm, and the thickness of the porous support layer is more than 20 μm, which can ensure good pressure resistance and obtain a defect-free and uniform support layer; if the thickness of the porous support film exceeds 100 μm, the residual amount of the reactant will increase during the preparation process, thereby causing the problem of reduced water flux and reduced chemical resistance.
[0053] In step (3) of the preparation method of the present invention, the porous support layer after being soaked in the aqueous solution contacts the organic solution, and the aqueous solution and the organic solution undergo interfacial polymerization at the interface to form a primary separation layer, which reacts for about 15 to 60 seconds to increase the bonding force between the polyamide and the support membrane; then the excess organic solution can be removed by means of an air knife, a water bath, a dryer, etc. During the interfacial polymerization reaction or after the organic phase is removed, ultraviolet light is irradiated for ultraviolet light curing, and the total time of ultraviolet light irradiation is 1 second to 20 minutes, preferably 5 to 60 seconds in order to achieve industrial production, so that the primary separation layer is further cross-linked and the performance of the composite reverse osmosis membrane is improved.
[0054] The present invention also provides a composite reverse osmosis membrane, which exhibits a water flux of at least 35 gfd and a NaCl removal rate of at least 99.3% when exposed to deionized water containing 2000 ppm NaCl at 25±0.5°C, pH=7.5±0.2 and a pressure of 1.55±0.02 MPa.
[0055] The present invention is further described below by means of specific examples, but it should not be understood that the present invention is limited thereto.
[0056] Where specific experimental steps or conditions are not specified in the examples, the corresponding conventional experimental steps or conditions in the art can be used. The reagents used without specifying the manufacturer are all conventional reagents available in the art.
[0057] The raw material source information in the following embodiments is shown in Table 1 below:
[0058] Table 1
[0059]
[0060] The method used to test the performance of the permeable membrane in the following embodiments is:
[0061] 1. Desalination rate (NaCl removal rate):
[0062] The test solution with a temperature of 25±0.5°C, pH of 7.5±0.2 and a sodium chloride concentration of 2000ppm was supplied to the composite reverse osmosis membrane under an operating pressure of 1.55MPa for membrane filtration. The conductivity of the supply water and the permeate water was measured with a Mettler conductivity meter; the desalination rate of NaCl was calculated based on the conductivity obtained and the following formula.
[0063] Desalination rate (%) = 100 × {1-(NaCl concentration in permeate water / NaCl in feed water)}
[0064] 2. Water flux (permeable water volume)
[0065] In the above test, the membrane permeation of the supplied water was measured, and the value converted to water flux per square inch per day (gallons) was taken as the membrane permeation flux (gfd).
[0066] 3. Acid and alkali resistance test (durability)
[0067] The composite reverse osmosis membrane was immersed in a sodium hydroxide aqueous solution with a pH of 13 for 20 hours, then rinsed with deionized water, and then immersed in a sulfuric acid aqueous solution with a pH of 1 for 20 hours. The above operation was counted as an acid-base cycle test.
[0068] The test was repeated for 5 cycles, the membrane was taken out and rinsed, and the desalination rate of the composite reverse osmosis membrane was tested according to the above desalination rate method.
[0069] Example 1
[0070] Preparation of Acrylate Nanopolymers:
[0071] 740 g of deionized water and 5.4 g of sodium dodecyl sulfate were stirred and dissolved uniformly, and 902 g of methyl methacrylate, 645 g of butyl acrylate and 48 g of acrylic acid were added under stirring, and the pre-emulsion of acrylic acid monomer was obtained after emulsification;
[0072] Add 12.6 grams of sodium dodecyl sulfate and 1050 grams of deionized water to a three-necked flask with a stirrer, stir and dissolve, and heat the materials to 88-90°C under nitrogen; add ammonium persulfate solution (2.1 grams of ammonium persulfate dissolved in 20 grams of deionized water) to the flask, and then uniformly drop the above-prepared monomer pre-emulsion and ammonium persulfate solution (2.1 grams of ammonium persulfate dissolved in 100 grams of deionized water) into the three-necked flask within 3 hours. The reaction temperature is maintained at 84-86°C, and the temperature is kept for 2 hours after the addition is completed to obtain an acrylate nanopolymer.
[0073] According to calculation and analysis, the added amount of carboxyl monomer in the nano polymer is 3wt%, the Tg of the nano polymer is 40°C, the particle size is 45nm, and the effective solid content is 45wt%.
[0074] (1) 2588 g of deionized water was added to a 5-liter dissolution tank, and 96 g of MPD, 180 g of TEACSA, 133 g of the above-prepared nanopolymer and 3 g of SLS were added under stirring to prepare an aqueous phase solution containing 2 wt % of nanopolymer (calculated according to effective solid content), 3.2 wt % of MPD, 6 % of TEACSA and 0.1 wt % of SLS;
[0075] Add 996g of ISOAR-G into a 2-liter organic batching tank, start stirring, add 2g of TMC and 2g of photoinitiator BP, and dissolve evenly to form an organic phase solution containing 0.2wt% TMC and 0.2wt% photoinitiator BP;
[0076] (2) pouring a 16.8 wt % DMF solution containing polysulfone (PSF) onto a polyester nonwoven fabric at 25° C., immediately immersing the fabric in pure water, and allowing the mixture to stand for 3 minutes, thereby preparing a porous support layer having a thickness of 45 μm;
[0077] The porous support membrane layer formed above was cut into 14×20 cm, placed flat on a glass plate, and the four sides were clamped with frames to form a groove. 50 mL of the aqueous solution obtained above was poured into the groove and the surface of the support layer, and the contact was maintained for at least 10 seconds. Then, the plate frame was tilted to pour out the excess aqueous solution, and the excess liquid on the surface of the porous support layer was removed by an air knife;
[0078] (3) Pour 50 ml of the organic phase solution prepared above onto the treated support layer surface and keep it in contact for 20 seconds, then drain the excess organic phase solution by tilting, and then dry it in an oven at 90°C for 6 minutes. After drying, use ultraviolet light to irradiate for 20 seconds for photocuring to obtain a composite reverse osmosis membrane.
[0079] Example 2
[0080] A composite reverse osmosis membrane was prepared by referring to the method of Example 1, except that the amount of photoinitiator added was 0.5 wt % and the ultraviolet light irradiation time was 60 s.
[0081] Example 3
[0082] Acrylate nanopolymer was prepared by referring to the method of Example 1, except that 770 g of methyl methacrylate, 745 g of butyl acrylate, 80 g of acrylic acid and 740 g of deionized water were added to the pre-emulsion monomer.
[0083] According to calculation and analysis, the added amount of carboxyl monomer (acrylic acid) is 5wt%, the Tg of the nano polymer is 30°C, the particle size is 75nm, and the effective solid content is 45wt%.
[0084] The process of preparing the composite reverse osmosis membrane is different from that of Example 1 in that 5 wt % of the above-prepared acrylate nanopolymer (calculated based on the effective solid content) is added to the aqueous phase in step (1).
[0085] Example 4
[0086] Preparation of Acrylate Nanopolymers:
[0087] 740 g of deionized water and 5.4 g of sodium dodecyl sulfate were stirred and dissolved uniformly, and 918 g of methyl methacrylate, 550 g of butyl acrylate and 128 g of acrylic acid were added under stirring, and the mixture was emulsified to obtain an acrylate monomer pre-emulsion;
[0088] Add 5.6 grams of sodium dodecyl sulfate and 1050 grams of deionized water to a three-necked flask with a stirrer, stir and dissolve, and heat the materials to 88-90°C under nitrogen; add ammonium persulfate solution (2.1 grams of ammonium persulfate dissolved in 20 grams of deionized water) to the flask, and then, uniformly drop the above-prepared monomer pre-emulsion and ammonium persulfate solution (2.1 grams of ammonium persulfate dissolved in 100 grams of deionized water) into the three-necked flask within 3 hours. The reaction temperature is maintained at 84-86°C, and the temperature is kept for 2 hours after the addition is completed to obtain an acrylate nanopolymer.
[0089] According to calculation and analysis, the added amount of carboxyl monomer (acrylic acid) is 8 wt %, the Tg of the nano polymer is 50° C., the particle size is 120 nm, and the effective solid content is 45 wt %.
[0090] The process of preparing the composite reverse osmosis membrane is different from that of Example 1 in that 5 wt % of the above-prepared acrylate nanopolymer (calculated based on the effective solid content) is added to the aqueous phase in step (1).
[0091] Example 5
[0092] Acrylate nanopolymer was prepared by referring to the method of Example 1, except that 955 g of methyl methacrylate, 450 g of butyl acrylate, 191 g of acrylic acid and 740 g of deionized water were added to the pre-emulsion monomer.
[0093] According to calculation and analysis, the addition amount of carboxyl monomer acrylic acid is 12wt%, the Tg of the nano polymer is 60°C, the particle size is 100nm, and the effective solid content is 45wt%.
[0094] The process of preparing the composite reverse osmosis membrane is different from that of Example 1 in that 5 wt % of the above-prepared acrylate nanopolymer (calculated based on the effective solid content) is added to the aqueous phase in step (1).
[0095] Example 6
[0096] Acrylate nanopolymer was prepared by referring to the method of Example 1, except that 912 g of methyl methacrylate, 555 g of butyl acrylate, 128 g of hydroxyethyl methacrylate and 740 g of deionized water were added to the pre-emulsion monomer.
[0097] According to calculation and analysis, the addition amount of hydroxyl monomer (hydroxyethyl methacrylate) is 8 wt %, the Tg of the nano polymer is 45° C., the particle size is 150 nm, and the effective solid content is 45 wt %.
[0098] The process of preparing the composite reverse osmosis membrane is different from that of Example 1 in that 5 wt % of the above-prepared acrylate nanopolymer (calculated based on the effective solid content) is added to the aqueous phase in step (1).
[0099] Example 7
[0100] Acrylate nanopolymer was prepared by referring to the method of Example 1, except that 920 g of methyl methacrylate, 580 g of butyl acrylate, 48 g of acrylic acid, 48 g of hydroxyethyl methacrylate and 740 g of deionized water were added to the pre-emulsion monomer.
[0101] According to calculation and analysis, the total amount of hydroxyl monomer and carboxyl monomer added is 6wt%, the Tg of the nano polymer is 45°C, the particle size is 75nm, and the effective solid content is 45wt%.
[0102] The process of preparing the composite reverse osmosis membrane is different from that of Example 1 in that 8 wt % of the above-prepared acrylate nanopolymer (calculated based on the effective solid content) is added to the aqueous phase in step (1).
[0103] Comparative Example 1
[0104] (1) Add 2721 g of deionized water into a 5-liter dissolution tank, add 96 g of MPD, 180 g of TEACSA and 3 g of SLS under stirring, and finally prepare an aqueous phase solution of 3.2 wt % MPD, 6 wt % TEACSA and 0.1 wt % SLS;
[0105] Add 998g of ISOAR-G into the organic batching tank, start stirring and add 2g of TMC, and dissolve evenly to form an organic phase solution containing 0.2wt% TMC;
[0106] (2) pouring a 16.8 wt % DMF solution containing polysulfone (PSF) onto a polyester nonwoven fabric at 25° C., immediately immersing the fabric in pure water, and allowing the mixture to stand for 3 minutes, thereby preparing a porous support layer having a thickness of 45 μm;
[0107] The porous support membrane layer formed above was cut into 14×20 cm, placed flat on a glass plate, and the four sides were clamped with frames to form a groove. 50 mL of the aqueous solution obtained above was poured into the groove and the surface of the support layer, and the contact was maintained for at least 10 seconds. Then, the plate frame was tilted to pour out the excess aqueous solution, and the excess liquid on the surface of the porous support layer was removed by an air knife;
[0108] (3) Pour 50 ml of the organic phase solution prepared above onto the treated support layer surface and keep it in contact for 20 seconds, then drain the excess organic phase solution by tilting, and then dry it in an oven at 90°C for 6 minutes. After drying, use ultraviolet light to irradiate for 20 seconds for photocuring to obtain a composite reverse osmosis membrane.
[0109] Comparative Example 2
[0110] Acrylate nanopolymer was prepared by referring to the method of Example 1, except that the amount of carboxyl monomer added to the nanopolymer was 5 wt %;
[0111] The composite reverse osmosis membrane was prepared by referring to the method of Example 1, except that 20 wt % of acrylate nanopolymer was added to the aqueous solution.
[0112] Comparative Example 3
[0113] Acrylate nanopolymer was prepared by referring to the method of Example 1, except that 1002 g of methyl methacrylate, 593 g of butyl acrylate and 740 g of deionized water were added to the pre-emulsion monomer.
[0114] The composite reverse osmosis membrane was prepared by referring to the method of Example 1, except that 5 wt % of the above-prepared acrylate nanopolymer (calculated based on the effective solid content) was added to the water phase.
[0115] The addition amount of raw materials in the above-mentioned implementation process is specifically summarized in the following Table 2:
[0116] Table 2
[0117]
[0118] The composite reverse osmosis membrane prepared above was subjected to performance testing, and the results are shown in Table 3 below:
[0119] Table 3
[0120]
[0121]
[0122] It can be seen from the above test results that compared with Comparative Example 1, the composite reverse osmosis membrane method provided by the present invention adds functional additives to the aqueous phase solution and the organic phase solution, and forms a separation functional layer on the porous support membrane through interfacial polymerization of polyamine compounds and polyacyl chloride compounds, thereby greatly improving the water flux and acid and alkali washing resistance of the composite membrane.
[0123] Compared with the blank membrane (Comparative Example 1), the reverse osmosis membrane prepared by adding acrylate nanopolymers to the aqueous phase and adding photoinitiators to the organic phase solution has the effect of improving flux and maintaining the desalination rate after frequent acid and alkali cleaning. It was observed that the water flux of the best case was increased by nearly 30% compared with the blank membrane, and the desalination rate was still able to remain above 99% after multiple acid and alkali cleanings.
Claims
1. A method for preparing a composite reverse osmosis membrane, characterized in that: include: (1) adding a polyamine compound and an additive into water, stirring and dissolving them at room temperature to prepare an aqueous phase solution; Adding polyacyl chloride compound and photoinitiator into non-polar solvent, stirring and dissolving at room temperature to prepare organic phase solution; (2) immersing the porous support layer in the aqueous solution prepared in step (1); (3) contacting the porous support layer treated in step (2) with the organic phase solution to perform interfacial polymerization, thereby forming a polyamide separation layer on the surface of the porous support layer, and the polyamide separation layer is cured by ultraviolet light to obtain a composite reverse osmosis membrane; Wherein, the additive in step (1) is selected from acrylic ester nanopolymers.
2. The preparation method according to claim 1, characterized in that: Based on the total weight of the aqueous solution, the amount of the acrylic ester nanopolymer added is 0.1 to 15 wt%, preferably 1 to 10 wt%; The particle size of the acrylic ester nanopolymer is 10 to 200 nm, preferably 30 to 150 nm, and the glass transition temperature is 10 to 80° C., preferably 20 to 60° C.
3. The preparation method according to claim 2, characterized in that: The acrylic acid ester nano polymer is prepared by reacting a carboxyl monomer and / or a hydroxyl monomer with an unsaturated double bond-containing monomer; Based on the total amount of raw materials added being 100 wt %, the amount of the carboxyl monomer and the hydroxyl monomer added is 0.5 to 15 wt %.
4. The preparation method according to claim 3, characterized in that: The unsaturated double bond-containing monomer is selected from one or more of styrene, acrylate, methacrylate, vinyl acetate, polyethylene glycol methyl ether acrylate, polyethylene glycol methyl ether methacrylate or N-vinyl pyrrolidone; The carboxyl monomer is selected from one or more of acrylic acid, methacrylic acid or itaconic acid; The hydroxy monomer is selected from one or more of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate or hydroxypropyl methacrylate.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The polyamine compound is selected from one or more of p-phenylenediamine, m-phenylenediamine, ethylenediamine, propylenediamine or piperazine; The polyacyl chloride compound is selected from one or more of trimesoyl chloride, trimellitic acid chloride or terephthaloyl chloride; The non-polar solvent is at least one selected from ethylcyclohexane, octane, nonane, decane, ISOPAR-E, ISOPAR-L and ISOPAR-G.
6. The preparation method according to claim 5, characterized in that: The aqueous phase solution is also added with a surfactant and a desiccant; Preferably, the surfactant and the desiccant are added in an amount of 0.1 to 10 wt % based on the total weight of the aqueous solution; More preferably, the surfactant is selected from nonionic surfactants, ionic surfactants and zwitterionic surfactants.
7. The preparation method according to any one of claims 1 to 6, characterized in that: Based on the total weight of the organic phase solution, the amount of the polyacyl chloride compound added is 0.05-1wt%, and the amount of the photoinitiator added is 0.05-5wt%; Preferably, the photoinitiator is selected from benzophenone derivatives, alkyl aromatic ketone derivatives, benzil derivatives or thioxanthone derivatives.
8. The preparation method according to any one of claims 1 to 7, characterized in that In step (2), the porous support layer is immersed in the aqueous solution for 10 seconds to 60 seconds, and then the excess solution on the membrane surface is removed; Preferably, the porous support layer is selected from a polysulfone porous support layer; More preferably, the thickness of the porous support layer is 20-100 μm.
9. The preparation method according to claim 8, characterized in that: In the ultraviolet light curing treatment of step (3), the ultraviolet light irradiation time is 1 second to 20 minutes.
10. A composite reverse osmosis membrane prepared by the preparation method according to any one of claims 1 to 9, characterized in that: When the composite reverse osmosis membrane is exposed to deionized water containing 2000 ppm NaCl at 25±0.5°C, pH=7.5±0.2 and a pressure of 1.55±0.02 MPa, it exhibits a water flux of at least 35 gfd and a NaCl removal rate of at least 99.3%.
Citation Information
Patent Citations
Large-flux contamination-resistant composite reverse osmosis membrane and preparation method thereof
CN102553458A
Interfacially synthesized reverse osmosis membrane
US4277344A
Use of inorganic ammonium cation salts to maintain the flux and salt rejection characteristics of reverse osmosis and nanofiltration membranes during drying
US5658460A
Compound reverse osmosis membrane with interpenetrating network desalting layer and preparation method of membrane
CN102921314A
Preparation method of polyamide composite membrane
CN117732285A